Evaluasi Ketidakseimbangan Beban Pada Penyulang Unicora - Ahmad Hermawan; Ahmad Koimam; Rhezal Agung Ananto; Satria Luthfi Hermawan (Elposys: Jurnal Sistem Kelistrikan, 2024)
Load imbalance in electrical distribution transformers can lead to significant power losses and decreased efficiency in electrical distribution systems. This study focuses on the load imbalance problem at the Unicora feeder of PT PLN (Persero) ULP Singosari, which hinders optimal operational efficiency. The purpose of this research is to evaluate the extent of load imbalance, its impact on power losses, and the effectiveness of load balancing interventions in mitigating these losses. The methodology includes phase load measurements from February to September 2021, analysis of load imbalance, and power loss simulations using ETAP 12.6.0 software. The study's important findings indicate that the average load imbalance decreased from 34% to 21% after implementing load balancing interventions. Concurrently, power losses in the neutral conductor were reduced from 106.3 kW to 78.0 kW. ETAP simulations revealed a total power loss of 773.5 kW in the Unicora feeder, underscoring the significant impact of load imbalance on system efficiency. The implications of this research are crucial for operational practices at PT PLN (Persero) ULP Singosari. The findings demonstrate that effective load balancing can significantly enhance distribution efficiency, reduce operational costs, and improve the reliability of electricity provision. This study advocates for continuous monitoring and adaptive management of load distribution in electrical networks to maintain optimal performance and sustainability.